Modeling the WELL concepts for residential buildings in developing countries: PLS-SEM approach - Salma Husna, Zamani; Liyana, Mohamed Yusof; Naganathan, Hariharan; Rahimi, A. Rahman (American Society of Civil Engineers (ASCE), 2025)
This study aims to develop a multivariate model that examines the interrelationships among design criteria and concepts impacting health, well-being, and productivity (collectively referred to as WELL goals) in residential buildings of developing countries. The specific objectives are to (1) assess the relative criticality of design criteria in impacting WELL goals, (2) categorize the design criteria into concepts, and (3) examine the impact of these concepts on WELL goals. To achieve these objectives, 51 design criteria were identified through semistructured interviews and a systematic review, providing a basis for survey development. Then, a total of 114 survey responses were collected using purposeful and snowball sampling techniques. Finally, the survey data were analyzed using the analytic hierarchy process, factor analysis (FA), and partial least square structural equation modeling (PLS-SEM). The FA categorized 35 design criteria into two concepts for health: safety and services, and community and mind. For well-being, 14 design criteria were categorized into three concepts: services, safety and services, and community and mind. Similarly, productivity was characterized by 14 design criteria, categorized into three concepts: safety and services, community and mind, and mind and services. The PLS-SEM confirmed that all eight concepts impact their associated WELL goals. Notably, 21 design criteria exhibited interrelationships across multiple WELL goals. Five design criteria (legal, mechanical and electrical services, management services, recycling practice, and biophilia) demonstrated direct linkages across all three WELL goals. Conversely, others were specific to certain WELL goals, highlighting overlapping yet distinct impacts. These findings underscore the need for an integrated design approach that addresses these interconnected design criteria and concepts to optimize occupant outcomes in residential buildings in developing countries. The study originality lies in developing a multivariate interrelationship model among design criteria and concepts that impact WELL goals in residential buildings of developing countries.